Methodology for Testing the Impact of Encoding on VoIP Service Quality within the Heterogenous Network - Piotr LUBKOWSKI (Communications of International Proceedings, 2021)
Major challenges faced by contemporary VoIP communications services include ensuring a high level of security and accessibility as well as high quality of services (QoS). An implementation of anyone encoding algorithm may lead to quality degradation due to instantaneous network bandwidth. This article presents a methodology and results of testing the impact of popular encryption algorithms, including the SCIP encryption, on the quality of VoIP communications within broadband heterogenous networks. The SCIP (Secure Interoperability Protocol) was offered as a basic solution introduced by NATO for ensuring secure communication of various network devices over a resource-constrained network. The SCIP is a development of the FNDBT (Future Narrowband Digital Terminal) concept and it helps overcome secure voice communication problems within narrowband communication networks. The SCIP technology was designed to ensure interoperable end-to-end communication across different communications systems, starting from military radio communications through traditional telephone communications systems, satellite channels to VoIP and different types of mobile telephony. Measurement was done with a MultiDSLA tester and with the application of PESQ and POLQA methods. The aim of this paper is to present an assessment of the impact of encryption protocols on the perceived quality of VoIP transmission. The presented method of measurement, together with the proposed research methodology, provides an opportunity to determine the probability of availability of a VoIP service of acceptable quality in heterogeneous networks.
Keywords: VoIP Qos; Speech Encryption; Testing Methodology